1990
DOI: 10.1093/sleep/13.6.533
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Otolithic Vestibular Stimulation on Sleep

Abstract: This study evaluated the effects of otolithic vestibular stimulation in the form of a linearly accelerated parallel swing on nighttime sleep parameters and daytime sleep tendency in eight normal subjects. The protocol consisted of one adaptation night following by two motion nights, one adaptation night followed by two stationary nights, and two Multiple Sleep Latency Tests (MSLT), one motion and one stationary. On the motion nights, there was a decrease in stage 2 percentage as well as a facilitative effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 0 publications
2
56
1
Order By: Relevance
“…Sleep duration and frequency are increased in humans living in rotating rooms over a period of several days despite the absence of other motion sickness symptoms such as nausea (Graybiel et al, 1960). Furthermore, otolith stimulation via "rocking" has been demonstrated to enhance some stages of sleep and sleep efficiency (Woodward et al, 1990). In contrast, rapid or transient vestibular stimulation, such as falling, is sufficient to evoke a startle response (Yeomans et al, 2002) and wake an organism from sleep (Horner et al, 1997).…”
Section: Convergence Of Vestibular and Hypocretin Projectionsmentioning
confidence: 99%
“…Sleep duration and frequency are increased in humans living in rotating rooms over a period of several days despite the absence of other motion sickness symptoms such as nausea (Graybiel et al, 1960). Furthermore, otolith stimulation via "rocking" has been demonstrated to enhance some stages of sleep and sleep efficiency (Woodward et al, 1990). In contrast, rapid or transient vestibular stimulation, such as falling, is sufficient to evoke a startle response (Yeomans et al, 2002) and wake an organism from sleep (Horner et al, 1997).…”
Section: Convergence Of Vestibular and Hypocretin Projectionsmentioning
confidence: 99%
“…Only two studies were conducted, where the effect of the provided vestibular stimulation on sleep was analyzed based on physiological measurements including brain activity (Electroencephalogram, EEG). Both studies suggest a facilitated transition between wakefulness and sleep and to deeper sleep stages [7], [8]. However, in both studies the characteristics and the direction of the chosen movements were not particularly motivated.…”
Section: Introductionmentioning
confidence: 91%
“…Vestibular stimulation was obtained using a bed that swung with a moderate to low frequency of 0.25 Hz and a peak horizontal acceleration of 0.1 m/s 2 . Older studies have reported anecdotal but not statistical evidence for similar effects (Woodward et al, 1990). Bayer and colleagues (2011) argue that vestibular stimulation may enhance synchronicity in thalamo-cortical networks, caused by vestibular and somatosensory input to the thalamic nuclei, which could promote onset and maintenance of sleep.…”
Section: The Moving History Of Vestibular Stimulationmentioning
confidence: 99%